ANALYSIS OF ORGANIC CARBON FLUX IN THE GILAP CAVE, PONJONG SUB-DISTRICT, GUNUNG KIDUL DISTRICT, YOGYAKARTA, INDONESIA - , Sutanto Trijuni Putro ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research was conducted in Ponjong Sub-District, Gunungkidul, which is the part of Gunungsewu Karst area. The objectives of this research are: 1) Assessing the organic carbon contained in the dripwater, underground river flow and the surface river